IMPLEMENTATION OF FINANCIAL INFORMATION SYSTEMS IN IMPROVING TRANSPARENCY AND ACCOUNTABILITY IN THE MANPOWER, TRANSMIGRATION, ENERGY AND MINERAL RESOURCES SERVICE OF CENTRAL PAPUA PROVINCE - Ruatakurei, Marthina Martha; Sabandar, Sita Yubelina; Malissa, Mika (Journal of Entrepreneur, Business and Management, 2025)
This study aims to analyze the implementation of the Financial Information System (FIS) in improving transparency and accountability at the Office of Manpower, Transmigration, Energy, and Mineral Resources of Central Papua Province. Using a qualitative approach, data were collected through observations, interviews with ten employees, and documentation analysis. The research findings indicate that the adoption of FIS involves several key aspects, including integrated financial software, database management systems, employee training, standardized operating procedures, system integration, financial performance dashboards, stakeholder access, and periodic evaluations. Transparency enhancement efforts include regular financial report publication, open forums, online access to budget realization, financial information applications, third-party audits, and workshops on budget transparency. Furthermore, accountability improvement measures encompass performance indicators, accurate reporting systems, employee training, complaint handling teams, clear accountability reports, public evaluations, and financial system integration with annual audits. The study concludes that the implementation of FIS significantly enhances financial transparency and accountability, ensuring effective budget management and strengthening public trust in government financial administration.